1989
DOI: 10.1159/000293493
|View full text |Cite
|
Sign up to set email alerts
|

Familial Clustering in the Polycystic Ovarian Syndrome

Abstract: To assess the degree of familial clustering and the mode of inheritance of the polycystic ovarian syndrome (PCO), the prevalence of PCO-related symptoms among first- and second-degree relatives of 132 PCO patients and 71 controls was studied using questionnaire data. 19.7% of male first-degree relatives of PCO patients were reported to have early baldness or excessive hairiness, as opposed to 6.5% of relatives of controls. For female first-degree relatives, the percentages for PCO-related symptoms were 31.4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
78
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(85 citation statements)
references
References 9 publications
(15 reference statements)
3
78
0
4
Order By: Relevance
“…Familial clustering seen in this syndrome suggests contribution of a genetic component to its pathogenesis (12,13). Over the past decade, a number of candidate genes involved in steroidogenesis, insulin signaling pathway, gonadotropin secretion and chronic inflammation have been explored to identify the susceptibility genes for PCOS (14,15); however, the results so far have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Familial clustering seen in this syndrome suggests contribution of a genetic component to its pathogenesis (12,13). Over the past decade, a number of candidate genes involved in steroidogenesis, insulin signaling pathway, gonadotropin secretion and chronic inflammation have been explored to identify the susceptibility genes for PCOS (14,15); however, the results so far have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…This has been investigated in several studies on PCOS phenotypes in different populations [17] and in family studies which indicated that a high number of female relatives are affected [18,19,20,21]. Most of these studies have used ovarian morphology [22,23] and endocrine abnormalities such as hyperandrogenaemia and anovulation to assign affected status [24].…”
mentioning
confidence: 99%
“…Familial aggregation of PCOS consistent with a genetic etiology has been well documented (4,5). The male reproductive phenotypes that have been proposed in PCOS families include abnormalities in hair distribution, such as increased hair growth (6), and more commonly balding (7)(8)(9)(10). This latter phenotype has been further refined to premature male balding defined as balding onset with an age of less than 30 yr (9,10).…”
mentioning
confidence: 99%